Comparing Efficacy of 35% Trichloroactetic Acid Versus 10% Potassium Hydroxide in Topical Treatment of Palmoplantar Warts in patients upto 12 years of age - Nazia Hanif, Raheel Tahir, Tahir Hassan, Muhammad Khurram Shahzad, Fahmida Malik, Zara Zaka (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Wart is a viral skin infection. Its etiological agent is human papilloma virus. It is composed of non-malignant proliferations of keratinocytes. Different regimens have been tried for the treatment of warts. 35% Trichloroacetic acid (TCA) is used conventionally but 10% KOH has shown promising results. Objective: To compare the efficacy of topical 35% Trichloroacetic acid (TCA) versus topical 10% Potassium Hydroxide (KOH) in the treatment of palmoplantar warts in children up to 12 years of age. Methods: A total of 148 cases of palmoplantar warts with age between 3-12 years of either gender were enrolled in the study. These cases were divided into two groups (A and B each having 74 patients). The patients in group A were treated with topical 35% TCA and Group B patients were treated with topical 10% KOH. Patients were followed weekly for 8 weeks for treatment and for further 8 weeks to look for recurrence. Final outcome was seen at 16 weeks. The efficacy was labelled as yes in cases with clearance of all disease lesions. Results: In this study overall patients were 148 with 74 cases in each group. Group A had 36 (48.65%) males and group B had 37 (50%). The mean age in group A was 7.42±2.48 and in group B was 7.81±2.50 years. Group A had 44 (59.46%) cases and group B had 47 (63.51%) cases, with age range of 8-12 years. The efficacy in group A was seen in 28 (37.84%) of cases while in group B it was seen in 57 (77.03%) cases. There were significantly better results seen in group B as compared to group A in terms of efficacy with p= 0.0001. Conclusion: The efficacy of 10% KOH is significantly better than 35% TCA and this difference is again significantly better in terms of all the confounding variables i.e. age, site, size and duration of warts.